PENERAPAN PENDIDIKAN KARAKTER MELALUI SEMBILAN PILAR KARAKTER ANAK USIA DINI (Studi pada TK Dharma Wanita Persatuan Sukoanyar Kecamatan Cerme Kabupaten Gresik) - Kusmiyati, Nia (Prodi Magister Manajemen Universitas Wijaya Putra, 2024)
This research aims to determine the implementation of character education through the nine pillars of early childhood character at the Dharma Wanita PBB Sukoanyar Kindergarten. The focus of the research is learning planning, implementation strategies, forms of activities, and supporting, inhibiting and solution factors. This type of research is descriptive qualitative. The results of this research describe that character education through the nine pillars of character at the Dharma Wanita PBB Sukoanyar Kindergarten has been implemented, but is not yet effective because in the learning planning and form of activities there are character pillars that have not been included in the RPPH so they have an impact on character. Where children are found who don't line up, throw rubbish carelessly, don't queue to wash their hands, don't shake hands, don't return toys, and like to fight. The supporting factors are the inclusion of learning planning in the KTSP and parental support. Meanwhile, the inhibiting factors are the absence of training in implementing character education, teacher confusion in planning and determining the form of children's activities and inadequate facilities and infrastructure. The solution is to hold sharing between school principals and teachers about children's character problems, and teachers' difficulties in implementing character education, the principal will program training and improve infrastructure.